2016
DOI: 10.1186/s13256-016-0869-8
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial aneurysms and optic glioma – an unusual combination: a case report

Abstract: BackgroundThe coexistence of glial high grade tumors (glioblastoma, anaplastic astrocytoma) and cerebral aneurysms is common but the association with optic glioma is rare. The treatment of these associated lesions is problematic.Case presentationA 36-year-old white woman presented to our institution with recurrent attacks of headache. Her preoperative radiological studies revealed a lesion of her left optic nerve with extension to the optic chiasma, an aneurysmatic dilatation of the left carotid bifurcation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
(35 reference statements)
1
3
0
2
Order By: Relevance
“…McKinney et al [ 3 ] provided evidence regarding the de novo formation of an AVM within an anaplastic oligodendroglioma in a patient and proposed the hypothesis that a hyperangiogenic stimulus provided by the tumor may have initiated the development of the AVM. A similar hypothesis was provided in previously proposed studies that claimed an increase in blood flow due to a higher blood supply to a malignant glioma may induce secondary changes in the arterial wall, thus stimulating the formation of aneurysms [ 4 , 5 ]. According to studies performed regarding C-X-C chemokine Receptor type 4 (CXCR4), Huang et al [ 6 ] demonstrated the association between CXCR4 with angiogenesis and tumor progression.…”
Section: Discussionsupporting
confidence: 71%
“…McKinney et al [ 3 ] provided evidence regarding the de novo formation of an AVM within an anaplastic oligodendroglioma in a patient and proposed the hypothesis that a hyperangiogenic stimulus provided by the tumor may have initiated the development of the AVM. A similar hypothesis was provided in previously proposed studies that claimed an increase in blood flow due to a higher blood supply to a malignant glioma may induce secondary changes in the arterial wall, thus stimulating the formation of aneurysms [ 4 , 5 ]. According to studies performed regarding C-X-C chemokine Receptor type 4 (CXCR4), Huang et al [ 6 ] demonstrated the association between CXCR4 with angiogenesis and tumor progression.…”
Section: Discussionsupporting
confidence: 71%
“…[ 22 , 23 ] The direct invasion and erosion of the vascular wall by tumor cells led to the formation of aneurysm. [ 3 , 24 , 25 ] However, epidermoid tumor is avascular, and there does not exist hemodynamic stress and hormonal effects contributing to the intracranial aneurysm formation. And the epidermoid tumor cell seldom directly invaded adjacent vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral aneurysms are seldom associated with primary intracranial tumor, which were reported in a wide range of tumor types, including meningioma, [ 1 ] glioma, [ 2 , 3 ] pituitary adenoma, [ 4 ] arachnoid cyst, [ 5 ] craniopharyngioma, [ 6 ] lymphoma, [ 7 , 8 ] and dermoid tumor. [ 9 ] It is estimated that the frequency of the association of primary brain tumor with intracranial aneurysm is approximately 1%.…”
Section: Introductionmentioning
confidence: 99%
“…1 Berbagai masalah intraoperasi pada tumor otak meliputi perdarahan intraoperasi, peningkatan tekanan intrakranial, kejang, hingga emboli udara dapat meningkatkan mortalitas dan morbiditas pasien. 2 Insiden tumor otak terjadi sekitar 24.55 per 100.000 orang. Dalam skala yang sangat kecil, tumor otak terjadi bersamaan dengan aneurisma otak, diestimasikan sebesar 0,5-4,5% kejadian.…”
Section: Pendahuluanunclassified